PREVALENCE OF MISSED NURSING CARE AMONG SENIOR NURSING STAFF - ANCHAL, A; NOOR, MJ; IMTIAZ, M; TESNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Missed nursing care (MNC) refers to the partial, delayed, or omitted delivery of essential patient care. It is a critical issue in healthcare systems worldwide, directly impacting patient safety, satisfaction, and outcomes. While extensively studied in developed nations, evidence from low- and middle-income countries, particularly Pakistan, remains limited. Objective: To evaluate the prevalence of MNC among senior nursing staff and identify contributing factors in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 245 registered nurses working in the ICU, ER, and other departments of Sir Ganga Ram Hospital, Lahore. Data were collected using an adapted questionnaire assessing MNC frequency and analyzed using SPSS. Descriptive statistics were calculated, and the reliability and validity of the tool were confirmed through Cronbach’s Alpha and Kaiser-Meyer-Olkin (KMO) measures. Results: The study found a high prevalence of MNC, with discharge planning (Mean = 2.77, SD = 1.14), patient ambulation (Mean = 1.79, SD = 0.99), and mouth care (Mean = 2.26, SD = 1.23) identified as the most frequently missed tasks. Contributing factors included excessive workload, resource shortages, and insufficient staffing. Nurses with less experience were more likely to report missed tasks, highlighting the importance of clinical exposure and training in reducing care omissions. Conclusion: Missed nursing care poses a significant challenge to healthcare quality and patient safety in Pakistan. Addressing these issues requires systemic reforms, including improved staffing ratios, resource allocation, and professional development programs. These findings provide valuable insights for policymakers and healthcare administrators to implement effective interventions aimed at mitigating MNC and enhancing nursing care quality.